2017
DOI: 10.3390/e19120693
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Thermodynamics: A Dynamical Systems Approach

Abstract: Abstract:In this paper, we develop an energy-based, large-scale dynamical system model driven by Markov diffusion processes to present a unified framework for statistical thermodynamics predicated on a stochastic dynamical systems formalism. Specifically, using a stochastic state space formulation, we develop a nonlinear stochastic compartmental dynamical system model characterized by energy conservation laws that is consistent with statistical thermodynamic principles. In particular, we show that the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The present work follows a long line of contributions within the control field to draw links between thermodynamics and control, see e.g., [6], [28], [25], [31], [30], [39]. More recently, important insights have linked the Wasserstein distance of optimal mass transport, which itself is a solution to a stochastic control problem, to the dissipation mechanism in stochastic thermodynamics [3], [2], [34], [13], [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work follows a long line of contributions within the control field to draw links between thermodynamics and control, see e.g., [6], [28], [25], [31], [30], [39]. More recently, important insights have linked the Wasserstein distance of optimal mass transport, which itself is a solution to a stochastic control problem, to the dissipation mechanism in stochastic thermodynamics [3], [2], [34], [13], [17].…”
Section: Discussionmentioning
confidence: 99%
“…Consider the expression in (30) for the power that can be drawn via a cyclic operation as discussed. Preparation of the ensemble, and actuation during the cycle, allow a number of choices.…”
Section: Fundamental Limits To Powermentioning
confidence: 99%
“…This constraint implies that the ith subsystem cannot supply any energy to the other subsystems or the environment, dissipate energy to the environment, nor be subject to stochastic energy fluctuations whenever its internal energy is zero. In this case, it can be shown that the resulting dynamical system is a non-negative dynamical system [12,30], and hence, scriptD=Rfalse¯+n, where Rfalse¯+n denotes the non-negative orthant of Rn. The input space U is assumed to be U=Rn.…”
Section: Stochastic Thermodynamic Modelmentioning
confidence: 99%
“…Damping (i.e. deceleration) of the system particles due to frictional effects leading to local heating of the fluid and resulting in entropy production, and the energy addition of the particles due to thermal fluctuations leading to local cooling of the fluid and resulting in entropy consumption, is evaluated using fluctuation theorems (see [12,13] and the numerous references therein). Thus, even though for stochastic thermodynamic models, the average entropy is positive (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These processes are another difference that NO reveals with conventional neurotransmitters. Consequently, modeling the dynamics of NO implies gathering in the model each and every one of its processes: synthesis or generation, diffusion, and self-regulation, with independence of the type of environment which is producing these dynamics, and for which we will use a nonlinear compartamental dynamical system model [34], [35].…”
Section: A Nitric Oxide Dynamic As Volume Signalmentioning
confidence: 99%